Criopreservação de mangabeira e jenipapeiro: desafios e perspectivas - Araújo, Anna Beatriz Nogueira de (2024)
The preservation of plant genetic resources has driven biotechnological research, especially in natural populations of species such as Genipa americana (genipap) and Hancornia speciosa Gomes (mangaba). These plants are of significant socioeconomic and cultural importance in Brazil, particularly in the state of Sergipe, due to their potential uses in cooking and medicine. The aim of this study was to develop and optimize in vitro conservation protocols for Genipa americana L. and Hancornia speciosa Gomes to preserve germplasm and genetic resources. Two experiments were conducted to develop conservation protocols for both species. For mangaba, the droplet vitrification technique was used, where shoot tips were exposed to the PVS2 solution for three lengths of time (10, 20, and 30 minutes). The results indicated that prolonged exposure to the PVS2 vitrification solution (30 minutes) affects regeneration of cryopreserved explants. Adding antioxidants to the solution or reducing exposure time may enhance the efficacy of this method. In the case of genipap, shoot tips were exposed to two encapsulation matrices with sodium alginate and calcium chloride [full-strength MS (100%) and ½ MS]). The encapsulation matrix plays a crucial role in protecting the shoot tips during cryopreservation, resulting in high regeneration rates after thawing. The full-strength MS matrix (100%) showed the best results. However, further optimizations are necessary to ensure the long-term viability of the explants.